Economic growth x environment: Forecasts for the Brazilian economy and its 5 macro regions, 2002 to 2012 - Joaquim Jose Martins Guilhoto; Ronaldo Seroa Motta; Ricardo Luis Lopes (European Regional Science Association (ERSA), 2002)
Using the MIBRA model, an Applied Interregional General Equilibrium Model, constructed for the Brazilian economy and its five macro regions (North, Northeast, Central West, Southeast, an South), this papers tries to identify which would be the impact of environmental restrictions in the economic growth of the Brazilian economy an in its macro regions, from 2002 to 2012. A basic scenario is constructed assuming that the environmental restrictions are as they are today, then, two other scenarios are constructed, one, assuming a severe environment control and other assuming a relaxation over the current environmental restrictions. To do so, some major environmental concerns are raised for each one of the Brazilian macro regions: a) for the North region, represented mainly by the Amazon rain forest, it is taken into the consideration the trade off between the area used by cattle raise and wood extraction with the area used by the rain forest; b) for the Northeast region, the main concern is the restriction on water use; c) for the Central West region, it is taken into consideration the expansion of the agriculture frontier and how it would affect the bio-diversity of the region; d) for the Southeast and South regions, the more industrialized regions, pollutants are a problem.
Keywords: 330